Clathrin Heavy Chain 1 Plays Essential Roles During Oocyte Meiotic Spindle Formation and Early Embryonic Development in Sheep - Han, Zhe; Hao, Xin; Zhou, Cheng-Jie; Wang, Jun; Wen, Xin; Wang, Xing-Yue; Zhang, De-Jian; Liang, Cheng-Guang (Frontiers in Cell and Developmental Biology, 2021)
As a major protein of the polyhedral coat of coated pits and vesicles, clathrin molecules have been shown to play a stabilization role for kinetochore fibres of the mitotic spindle by acting as inter-microtubule bridges. Clathrin heavy chain 1 (CLTC), the basic subunit of the clathrin coat, plays vital roles in both spindle assembly and chromosome congression during somatic-cell mitosis. However, its function in oocyte meiotic maturation and early embryo development in mammals, especially in domesticated animals, has not been fully investigated. In this study, the expression profiles and functional roles of CLTC in sheep oocytes were investigated. Our results showed that the expression of CLTC was maintained at a high level from the germinal vesicle (GV) stage to metaphase II stage, and that CLTC was distributed diffusely in the cytoplasm of cells at interphase, from the GV stage to the blastocyst stage. After germinal vesicle breakdown (GVBD), CLTC co-localized with beta-tubulin during metaphase. Oocyte treatments with taxol, nocodazole, or cold did not affect CLTC expression levels, but led to disorders of its distribution. Functional impairment of CLTC by specific morpholino injections in GV stage oocytes led to disruptions in spindle assembly and chromosomal alignment, accompanied by impaired first polar body (PB1) emissions. In addition, knockdown of CLTC before parthenogenetic activation disrupted spindle formation and impaired early embryo development. Taken together, the results demonstrate that CLTC plays a vital role in sheep oocyte maturation via the regulation of spindle dynamics, and an essential role during early embryo development.